Management of Governance and Distribution of Animal Slaughter in Indonesia - Faqih Faqih; Abdul Sattar (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the permissibility of slaughtering and distributing dam animals outside the Holy Land, including Indonesia, based on the opinions of contemporary scholars and fatwa institutions. This issue is important because of the emergence of the 2024 Indonesian Hajj Mudzakarah policy which permits the slaughter and distribution of dam meat outside the Holy Land, including Indonesia. This study uses a qualitative approach with a descriptive approach and library research. This study produced three findings that permit the slaughter of dam meat in Indonesia: the opinions of Ath-Thabari, the Maliki School, the Hanbali School, and the Egyptian Darul Ifta Fatwa, which emphasizes the aspects of welfare and youth for Hajj pilgrims. Meanwhile, two opinions prohibit it, namely Imam Shafi'i and Imam Abu Hanifah, according to which the slaughter of dam meat must be carried out in the Holy Land according to sharia. These results show the flexibility of Islamic law that can be considered in a modern context, especially in the implementation of the Hajj pilgrimage which is oriented towards social welfare.